Construction of inter‐chain polymers and the investigation into Friedel–Crafts alkylation of styrene–acrylonitrile copolymers with chloroprene rubber and characterization. Issue 8 (12th September 2020) - Wei, Xuefeng; Zhang, Pengcheng; Cui, Shen; Che, Wei; Zhao, Jiruo; Feng, Ying
Abstract: In this study, the Friedel–Crafts alkylation was realized in a solvent free processing of styrene–acrylonitrile copolymers/chloroprene rubber (SAN/CR) molten blending which contributes the formation of SAN‐co‐CR co‐polymers and improved compatibility between SAN and CR. The properties of several Lewis acid compounds were tested as catalysts among which AlCl3 was the most efficient. The effects of blending temperature and time on the co‐polymer formation in situ were also investigated. The methodology of weighing and Fourier transform infrared analyses indicated that the reaction degree increases with increasing blending temperature and time in the ranges of this study. The micro‐structures and reaction mechanisms of the resulted SAN‐co‐CR polymers and morphological structures of SAN/CR/AlCl3 blends were characterized as well by differential scanning calorimetry, FT‐IR spectra, GPC and scanning electron microscopy. The results showed that the inter‐facial reactions between SAN and CR have been effectively improved. Moreover, the inter‐chain structure of SAN‐co‐CR co‐polymers was proposed which is different from general grafting or blocking co‐polymers. Abstract :